2020
DOI: 10.1101/2020.11.25.395376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes and Practices of Open Data, Preprinting, and Peer-review - a Cross Sectional Study on Croatian Scientists

Abstract: Attitudes towards open peer review, open data and use of preprints influence scientists’ engagement with those practices. Yet there is a relatively small number of validated questionnaires that measure these attitudes. The goal of our study was to construct and validate such a questionnaire. Using a sample of Croatian scientists (N=541), from a wide range of disciplines, we developed a questionnaire titled Attitudes towards Open data sharing, preprinting, and peer-review (ATOPP). The questionnaire has 21 item … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…First, due to the low response rate our ndings are not necessarily generalizable (we discuss possible in uences of self-selection and non-response biases in detail in the Appendix). Our response rate, however, was similar to other recent large online surveys, 22,[33][34][35][36] and response rates have been consistently found to be lower in online versus other modes of survey dissemination. 37 The recent exception to this pattern was a 2019 survey of 2,801 researchers from economics, political science, psychology, and sociology regarding open science practices, which had a response rate of 46%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, due to the low response rate our ndings are not necessarily generalizable (we discuss possible in uences of self-selection and non-response biases in detail in the Appendix). Our response rate, however, was similar to other recent large online surveys, 22,[33][34][35][36] and response rates have been consistently found to be lower in online versus other modes of survey dissemination. 37 The recent exception to this pattern was a 2019 survey of 2,801 researchers from economics, political science, psychology, and sociology regarding open science practices, which had a response rate of 46%.…”
Section: Discussionsupporting
confidence: 89%
“…Further research is warranted to determine national or institutional differences. 36,38 Third, although our survey was con dential, previous research has suggested that researchers often overestimate detrimental research practices of their colleagues, 27 but may also underreport such practices in order to protect the reputation of their eld or themselves, for being unwilling to report such practices for o cial investigations. 39 Fourth, to preserve con dentiality, we did not ask information on respondents departments or universities.…”
Section: Discussionmentioning
confidence: 92%
“…Researchers who had authored a preprint also rated the benefits of preprints higher, and had fewer concerns about them, than those who had not posted one, suggesting that familiarity with preprinting may help mitigate some of the concerns stakeholders have. A 2020 survey among Croatian researchers on attitudes and practices around open data, open peer review and preprinting, also found that those who had posted preprints expressed a positive attitude about preprinting, although it is important to note that only a minority (11 per cent) of respondents had previously posted a preprint, and the attitude towards preprinting was neutral overall across the full sample (Baždarić et al, 2020).…”
Section: Authorsmentioning
confidence: 99%